2021
DOI: 10.1097/mao.0000000000003144
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mirror Biofeedback Rehabilitation on Synkinesis in Acute Stage Facial Palsy in Children

Abstract: Objectives:To evaluate the efficacy of mirror biofeedback rehabilitation for synkinesis in severe acute facial paralysis in children.Methods:Eight pediatric patients with facial paralysis with an initial electroneurography (ENoG) value less than 10% who underwent mirror biofeedback rehabilitation (the child-rehabilitation group) were enrolled. Seven infants (under age 2 yr) who were unable to undergo rehabilitation (the infant-and-toddler control group) and adult patients (n = 13, range, 33–56 yr) who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In addition, this patient was administered home therapies, including facial massage, biofeedback, and warm compresses three times a day with a duration of 10 minutes. Studies have demonstrated that these therapies can facilitate muscle relaxation and improve muscle tone, as well as stimulate muscle strength through specific movements in front of a mirror (Baba et al, 2021;Dewi et al, 2020). In this case, the parents have high expectations that their daughter will achieve symmetrical lips similar to those of other children, given her psychosocial development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this patient was administered home therapies, including facial massage, biofeedback, and warm compresses three times a day with a duration of 10 minutes. Studies have demonstrated that these therapies can facilitate muscle relaxation and improve muscle tone, as well as stimulate muscle strength through specific movements in front of a mirror (Baba et al, 2021;Dewi et al, 2020). In this case, the parents have high expectations that their daughter will achieve symmetrical lips similar to those of other children, given her psychosocial development.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the parents have high expectations that their daughter will achieve symmetrical lips similar to those of other children, given her psychosocial development. The prognosis for peripheral facial palsy in children is likely to be more favorable than in adults (Baba et al, 2021). Should the patient's condition at the end of therapy fall short of parental expectations, it is recommended that they undergo dynamic facial reanimation surgery, with a recovery outcome of more than 80%, and crossfacial nerve grafting, with a recovery outcome of more than 83% (Ciorba et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment modalities include patient education, massage/stretching, facial tapping, functional and facial expression retraining, electrical stimulation, biofeedback therapy, and more [19]. Despite some concerns that physical therapy in the early stages of facial paralysis can increase the risk of synkinesis, recent studies have shown improved functional outcomes with either no change or a decrease in the development of synkinesis [20 ▪▪ ,21,22 ▪ ]. There is thought that electrical stimulation could reduce the sequelae of facial paralysis by preventing muscle atrophy and improving the selectivity of motor nerve regeneration; however, study results vary.…”
Section: Physical Therapymentioning
confidence: 99%
“…7 The electroneurography (ENoG) value of <40% and the ratio of the interpalpebral distance of <85% [8][9][10] have been reported to be correlated with the occurrence of synkinesis. Based on our previous studies, [11][12][13][14][15][16][17] we hypothesized that the characteristics of patients with early-onset facial paralysis measured with values of "ENoG," "the difference in the nerve excitability test (NET)," and "Yanagihara score" could be used to exquisitely predict facial synkinesis using machine learning (ML). Previous studies demonstrated the effectiveness of ML models in predicting clinical outcomes in numerous medical conditions, as well as in identifying prognostic factors.…”
Section: Introductionmentioning
confidence: 99%